Development of Problem-Based Learning Devices to Improve Mathematics Problem Solving Ability and Learning Independence of Labuhanbatu Private Junior High School Students - Sudirman; Dedy Juliandri Panjaitan (PT Inovasi Pratama Internasional, 2023)
This development research generally aims to develop problem-based learning tools that are valid, practical and effective, in particular the objectives are to : 1) Produce product development problem-based learning tools that are valid, practical and effective in improving students' mathematical problem solving skills and independence . 2) Analyzing the increase in students' mathematical problem solving abilities in the application of problem-based learning tools. 3) Analyze the level of student learning independence in the application of learning tools. The researcher gave pretest questions to students to see students' initial abilities before being given the learning tools that had been developed. The data obtained from the results of the pretest and posttest were analyzed to find out how much the increase in students' learning independence abilities occurred. Testing of the assessment instrument was carried out at the beginning (pretest) and at the end (posttest) of the meeting. This learning tool was developed using a development model referring to Plomp's theory, which consists of five phases, namely the initial investigative research phase, the design phase, the design phase, the assessment phase and the implementation phase (trial). LKPD is another tool that was developed using a problem-based learning model for problem-solving abilities and participants' independent learning abilities that can be said to be effective, valid and practical.